ICT uses by rural youth in Kenya: Perspectives from the Vijabiz project - Wahiu, Richard; Lohento, Ken; Koutchade, Folake (Technical Centre for Agricultural and Rural Cooperation, 2020)
This study is produced in the framework of activities of the Vijabiz project implemented by CTA and Ustadi Foundation in Kenya. It aimed at establishing rural youth groups’ access and use of different ICT and social media in their agribusiness activities. The study also sought to assess the gaps and barriers affecting the use of ICTs by rural youth in Kenya and provide recommendations. ICTs are considered as any digital technology that facilitates access to, processing and dissemination of information. This includes the mobile phone, the computer, software including basic editing tools, the internet, satellites, digital radio, digital video, social media platforms such as Facebook and Instagram, etc. Qualitative and quantitative methods were used, leveraging on desk research, interviews and a survey. Examples of actual use of digital technologies, impacts on businesses, testimonies, challenges faced are provided in the report. It also includes recommendations to various stakeholders.